The Quality Measurement of Products, Services, and Advertising on Customer Satisfaction at Fast Food Restaurant in Bekasi Area (A Case Study at J. Co Donuts & Coffee) - Dovina Navanti; Abdul Rohman Taufik; Ikhwanul Hakim (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to examine how much influence Product Quality (X1), Service (X2), and Advertising (X3) have on Consumer Satisfaction (Y) at J. Co Donuts & Coffee. This research is a quantitative research with non-probability sampling method with accidental sampling technique. The population in this study are the students of the Economics Faculty, Universitas Bhayangkara Jakarta Raya, Management program. With a research sample of 146 people, using the accidental sampling formula. This research was conducted using the SPSS version 25 program. The result of the Coefficient of Determination Test for adjusted R square, was obtained at 0.571. This means that 57.1% while the remaining 42.9% is explained by other causes that are outside the variables of this study.